Study of drilling muds on the anti-erosion property of a fluidic amplifier in directional drilling - Jiang-fu He; Peng-yu Zhang; Qi-lei Yin; Kun Yin; Hou-ping Liu (Fracture and Structural Integrity)
Due to some drawbacks of conventional drilling methods and drilling tools, the application of hydraulic hammers with a fluidic amplifier have been extensively popularized since its emergence in recent years. However, the performance life of a fluidic amplifier is still unsatisfactory in oil and gas wells drilling, especially the heavy wear or erosion of the fluidic amplifier leads to the reduction of service life time of hydraulic hammers, which is derived from the incision of drilling muds with high speed and pressure. In order to investigate the influence of drilling muds, such as particle size, solid content and jet velocity, on the antierosion property of a fluidic amplifier, several groups of drilling muds with different performance parameters have been utilized to numerical simulation on basis of Computational Fluid Dynamics (CFD). Simulation results have shown that the jet nozzle of fluidic amplifiers is primarily abraded, afterwards are the lateral plates and the wedge of the fluidic amplifier, which shows extraordinary agreement with the actual cases of fluidic amplifier in drilling process. It can be concluded that particle size, solid content and jet velocity have a great influence on the anti-erosion property of a fluidic amplifier, and the erosion rate linearly varies with the particle size of drilling muds, nevertheless exponentially varies with solid content and jet velocity of drilling muds. As to improve the service life time of a fluidic amplifier, the mud purification system or low solid clay-free mud system is suggested in the operation of directional well drilling.